Effects of microwave heating on the quality characteristics and thermal properties of RBD palm olein - Tan, C.P; Che Man, Y. B.; S, Jinap; Yusoff, M.S.A (Elsevier Science, 2002)
In the present work, the influence of microwave power (low-, medium- and high-power settings) and heating time on lipid deterioration produced during the microwave heating of RBD palm olein (RBDPOO) was evaluated. The changes in thermal profiles by differential scanning calorimetry (DSC) were studied in comparison to the changes in chemical parameters. The DSC method was based on the cooling and melting curves of oils at a scanning rate of 5 °C/min. The chemical evaluation of the oils was based on free fatty acid content, C18:2/C16:0 ratio, peroxide, iodine, and anisidine values. The DSC results were explained on the basis of the endo- or exothermic peak temperatures. A statistical comparative study was carried out on the DSC and chemical parameters. The results indicate that there is a good correlation between the DSC and chemical methods. Based on the results obtained, the DSC appears to be a useful instrumental method in monitoring the oxidation of microwave heated oils, and it may have the potential to replace the time- and chemical-consuming standard chemical methods.